Save Our Pesantren: Curriculum Program and Deradicalization (A Study of Multiculturalism Programs in Pesantren) - Muhajir, Izzah Fitriani; Nawas, Zuhri Abu; Kartini, Kartini (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study analyzes the efforts of the Al-Muhajirien Islamic Boarding School in implementing the pesantren curriculum and deradicalization efforts within the pesantren environment. The purpose of this research is to understand the strategies or efforts used by the Al-Muhajirien Islamic Boarding School in integrating the Islamic boarding school curriculum with deradicalization efforts to prevent the spread of radical understanding among students as well as the supporting and inhibiting factors in its implementation. The method used in this research is qualitative research with a case study approach. Data were obtained through in-depth interviews with pesantren administrators, teachers, and students, as well as direct observation of the learning process and activities of the pesantren. The research results show that the Al-Muhajirien Islamic Boarding School has implemented the deradicalization approach into the pesantren curriculum. This effort involves using inclusive learning methods, open discussion of radical issues, and emphasizing moderate religious values. As a result, this pesantren has created an environment that teaches true spiritual understanding and encourages critical and rational thinking, effectively preventing radical views among students. This research provides insight into how Islamic boarding schools can support deradicalization through a holistic and essential curriculum approach.